Lean Operations in Tertiary Institutions: A Tool for Elimination of Waste in Technical Universities, Ghana - BAWA DUKPER, KOJO; Laar , Stephen; Boadu Asiama , Joseph (Archives of Business Research, 2022)
The application of lean operation systems in tertiary institutions has a potential benefits to many universities in Ghana. The focus of this study was to systematical evaluate the basic principles of lean management and its application to tertiary institutions by streamlining structures and models that will provide satisfactory services for customers by eliminating administrative wastes. The survey design was used with questionnaire as the instrument for data gathering. A random sampling strategy was applied in obtaining the sample size for the study. The findings of the study revealed seven different types of administrative waste where each of these wastes were ranked in terms of their magnitude within the university. Also, the indication of the result is that, over staffing the number of academic or administrative units and underutilization of talent of employees’ were the most essential component of waste identified. Therefore, the techniques and tools to guide the implementation of lean model in the university as proposed by the study is to establish norms and standards; focus on the value of the customer; use punitive measures as deterrents; adhere strictly to budget lines; establish workflow sequence; ensure effective communication and information; zero inventory as well as follow laid down administrative procedures. The novelty of this study is that, it provides concrete direction in implementing lean frameworks in all universities and helps streamline activities that will create value by mapping the streams to satisfy the needs of the university community.